Year of Pleasures a novel - Berg, Elizabeth (New York : Random House, 2005)
Betta Nolan moves to a small town after the death of her husband to try to begin anew. Pursuing a dream of a different kind of life, she is determined to find pleasure in her simply daily routines. Among those who help her in both expected and unexpected ways are the ten-year-old boy next door, three wild women friends from her college days, a twenty-year-old who is struggling to find his place in the world, and a handsome man who is ready for love.
91638
Keywords: Widows; Loss (Psychology); Female friendship; City and town life; Middle West; Psychological fiction; Love stories